Pengaruh Iklan dan Brand Image terhadap Minat Beli Produk EIGER Pasca Pandemi Covid-19: - Mangandar Sitanggang; Danang Kusnanto (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
The impact of advertisements and the brand image on interest in the purchase of the EIGER after covid-19 study in the millennial generation society of Kabupaten Karawang. Thesis Faculty of Economic, Singaperbangsa Karawang University. This new research is aimed at knowing the impact and impact of Advertising and the Brand Image on the interest of the purchase of a millennial society in the municipality of the stock market on the eiger products after the covid-19 pandemic. The sample in this study numbered 100 from the millennial society of Kabupaten Karawang. The study used validity, reliability and normality tests and t and test f tests to help with the study, and tests were done with SPSS AIDS, and Microsoft excel. Studies have concluded that the ikla and the brand image are positive and simultaneous effects on the purchase of EIGER after the covid-19 pandemic in millennial society of Kabupaten Karawang. Keyword: Advertising, Brand Image, Purchase.